Diffusion Coefficients in Aqueous Solutions of Cobalt Chloride at 298.15 K - Ribeiro, Ana C. F. (2002)
Differential diffusion coefficients of cobalt chloride in water at 298.15 K, and at concentrations from 8 × 10-3 mol dm-3 to 3 × 10-1 mol dm-3, have been measured using a conductometric cell and an automatic apparatus to follow diffusion. The cell uses an open ended capillary method and a conductometric technique is used to follow the diffusion process by measuring the resistance of a solution inside the capillaries, at recorded times. The results are discussed on the basis of the Onsager−Fuoss and Gordon models.